Phytochemical analysis and establishment of embryogenic cell suspension and agrobacteriummediated transformation for farmer preferred cultivars of west African plantain (Musa spp.) - Jekayinoluwa, T.; Tripathi, J.N.; Obiero, G.; Muge, E.; Tripathi, L. (MDPI, 2020)
Banana and plantain are among the foremost staple food crops providing food and livelihood to over 500 million people in tropical countries. Despite the importance, their production is hampered due to several biotic and abiotic stresses. Plant tissue culture techniques such as somatic embryogenesis and genetic transformation offer a valuable tool for genetic improvement. Identification and quantification of phytochemicals found in banana and plantain are essential in optimizing in vitro activities for crop improvement. Total antioxidants, phenolics, flavonoids, and tannins were quantified in various explants obtained from the field, as well as in vitro plants of banana and plantain cultivars. The result showed genotypic variation in the phytochemicals of selected cultivars. The embryogenic cell suspensions were developed for three farmer-preferred plantain cultivars, Agbagba, Obino l’Ewai, and Orishele, using different MS and B5-based culture media. Both culture media supported the development of friable embryogenic calli (FEC), while MS culture media supported the proliferation of fine cell suspension in liquid culture media. The percentage of FEC generated for Agbagba, Obino l’Ewai, and Orishele were 22 ± 24%, 13 ± 28%, and 9 ± 16%, respectively. Cell suspensions produced from FECs were successfully transformed by Agrobacterium-mediated transformation with reporter gene constructs and regenerated into whole plants.